Reseña de Crespo Fernández, Eliecer (ed.) (2018): Taboo in Discourse: Studies on Attenuation and Offence in Communication - Mariscal Ríos, Alicia (Pragmalingüística, 2018)
Se trata de una reseña de Crespo Fernández, Eliecer (ed.) (2018): Taboo in Discourse: Studies on Attenuation and Offence in Communication.